2017
DOI: 10.1016/j.atmosres.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Origin and pathways of the mineral dust transport to two Spanish EARLINET sites: Effect on the observed columnar and range-resolved dust optical properties

Abstract: In this paper, is presented a method for estimation of the effect of the transport process to aerosol optical properties. Aerosol optical data retrieved by lidars and sun-photometer measurements, are applied to Saharan dust events observed simultaneously at the two EARLINET/AERONET sites of Barcelona and Granada during the periods of June-September of 2012 and 2013. For this purpose, elastic lidar profiles and sun-photometer columnar retrievals are analyzed together with satellite observations and dust forecas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…On the other hand, the source regions identified in this work are in agreement with those obtained by means of the potential source contribution function (PSCF) in Elche (southern VC; Nicolás et al, 2011). The same geographic area (Morocco and western Algeria) was identified by Mandija et al (2017) as the main source area in Barcelona (northeastern Spain) and Granada (southern Spain). Fig.…”
Section: Atmospheric Circulation Types That Trigger Sde In the Valencsupporting
confidence: 88%
“…On the other hand, the source regions identified in this work are in agreement with those obtained by means of the potential source contribution function (PSCF) in Elche (southern VC; Nicolás et al, 2011). The same geographic area (Morocco and western Algeria) was identified by Mandija et al (2017) as the main source area in Barcelona (northeastern Spain) and Granada (southern Spain). Fig.…”
Section: Atmospheric Circulation Types That Trigger Sde In the Valencsupporting
confidence: 88%
“…The city is medium-size with a population about 235000 inhabitants, which increases up to 530000 including the metropolitan area, and non-industrialized being its main aerosol sources the domestic heating based on fuel oil combustion in winter and the heavy traffic along all year (Lyamani et al, 2010(Lyamani et al, , 2011Titos et al, 2012Titos et al, , 2014. Columnar aerosol pattern in the area is characterized by higher values in summer mostly associated with Saharan dust arrivals (Pérez-Ramírez et al, 2012;Mandija et al, 2016), while the lowest aerosol loads usually corresponds to the arrivals of Atlantic air-masses that clean the atmosphere (Pérez-Ramírez et al, 2016).…”
Section: Instrumentation At Granada Stationmentioning
confidence: 99%
“…Navas-Guzmán et al, 2013), dust (e.g. Granados-Muñoz et al, 2016;Veselovskii et al, 2017) pollution (e.g. Wandinger et al, 2002;Noh et al, 2009;Veselovskii et al, 2013), and artic haze (Müller et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…During Sahara dust events, ambient PM concentrations increase significantly and the inhalation of high PM concentrations can cause serious problems to human health (Prospero 1999;Moreno et al 2006 and references therein;Goudie 2009;Pandolfi et al 2014;Mandija et al 2017). Some studies concluded that bioaerosols, like pollen, viruses, fungi and bacteria, can be attached to the dust transported (Griffin et al 2001;Kellogg and Griffin 2003).…”
mentioning
confidence: 99%